A study on methods that Facebook users in Singapore perceive as effective for food and beverage businesses in attracting and engaging fans through Facebook pages. - Mesy. (2012)
This research project aims to learn about the methods which Facebook users perceive as effective for food and beverage (F&B) businesses in Singapore in attracting and engaging Facebook fans. We have adapted the website visitor attraction and retention techniques proposed by Miletsky (2010) to study the fan-attraction and fan-engagement methods for the F&B Facebook pages. In the survey, 342 responses were collected where respondents were asked to rate the likelihood of them becoming a fan of an F&B Facebook page and their interest level to engage with the page in response to a list of suggested methods. The results indicate that Miletsky’s techniques are applicable in marketing Facebook pages of F&B businesses. In particular, posting promotions on the Facebook pages is deemed to be the most effective method by the sampled respondents in both recruiting new fans and engaging existing ones. The implications and future research recommendations for the study are also discussed at the end of the report.